Recovery and Reduction of Non-Performing Loans – Podgorica Approach - Ristan Stijepović (Journal of Central Banking Theory and Practice, 2014)
Loan portfolio of Montenegro's banking sector was largely affected by the growth in past due loans during the current financial crisis. High level of these loans limits banks' lending activity which results in a decline in credit supply. Negative effects of the non-performing loans' growth reflected adversely on economic strength of the real and households sectors. Majority of Montenegrin companies have significant liquidity problems and their defaults affect adversely the sound part of the economy, while reduced households spending reflects negatively on aggregate demand. Therefore, a new approach for the recovery of these loans should be sought and reduce their negative impact on loan portfolio of the banking sector. The World Bank Financial Sector Advisory Centre (FinSac) located in Vienna proposed a series of measures and recommendations for the resolution of these loans through several modules. In addition to the strengthening of loan portfolio and initiating more dynamic lending activity of the banking sector, the project called Podgorica Approach aims at strengthening financial stability of the system, supporting debtors' recovery, and improving economic growth. Podgorica Approach contributed, in particular, to quantitative assessment of the recovery of non-performing loans which could return to the performing status through the restructuring process. Better qualitative understanding of these loans is necessary to act preventively and thus largely reduce migration from performing to non-performing loans. In addition, this approach aims at strengthening the incentives proposed by the authorities so that the level of non-performing loans is reduced through their successful implementation.
Keywords: G01; C25; C11; 330; Podgorica Approach; non-performing loans (NPLs); restructured loans; debt restructuring; incentives; financial stability of the system; debtors' recovery; economic growth